1996
DOI: 10.1108/01443579610110459
|View full text |Cite
|
Sign up to set email alerts
|

Set‐up reduction in pharmaceutical manufacturing: an action research study

Abstract: The Japanese approach to manufacturing has been well documented. Many European firms have successfully adopted and adapted a variety of Japanese manufacturing techniques. This paper describes how a pharmaceutical manufacturer responded to an increased requirement for manufacturing flexibility through the introduction of a key Japanese manufacturing technique, namely machine set‐up time reduction. An unusual feature of the study is the use of action research. The strong emphasis on participation and collaborati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 8 publications
0
18
0
3
Order By: Relevance
“…Lean operations/manufacturing Dov (1992) Food Batch CS Billesbach (1994) Textile Batch CS Ezingeard and Race (1995) Chemical Batch SIM, CS Welgama and Mills (1995) Pharmaceutical Batch CS Iijima, Komatsu, and Katoh (1996) Food Continuous CM, AR, CS Cook and Rogowski (1996) Chemical Continuous CS Gilmore and Smith (1996) Pharmaceutical Batch AR, CS Jones, Hines, and Rich (1997) Brewing Batch AR, CS Mileham et al (1999) Plastic Batch AR, CS Radnor (2000) Chemical also indicated in the literature that in recent times, use of VSM has been increased in process industries to implement lean (Abdulmalek and Rajgopal 2007;Seth, Seth, and Goel 2008;Jimenez et al 2011;Perez et al 2010;Upadhye, Deshmukh, and Garg 2010;Chowdary and George 2012). Literature also implies that quick changeover techniques are often implemented in batch process industries.…”
Section: Type Of Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Lean operations/manufacturing Dov (1992) Food Batch CS Billesbach (1994) Textile Batch CS Ezingeard and Race (1995) Chemical Batch SIM, CS Welgama and Mills (1995) Pharmaceutical Batch CS Iijima, Komatsu, and Katoh (1996) Food Continuous CM, AR, CS Cook and Rogowski (1996) Chemical Continuous CS Gilmore and Smith (1996) Pharmaceutical Batch AR, CS Jones, Hines, and Rich (1997) Brewing Batch AR, CS Mileham et al (1999) Plastic Batch AR, CS Radnor (2000) Chemical also indicated in the literature that in recent times, use of VSM has been increased in process industries to implement lean (Abdulmalek and Rajgopal 2007;Seth, Seth, and Goel 2008;Jimenez et al 2011;Perez et al 2010;Upadhye, Deshmukh, and Garg 2010;Chowdary and George 2012). Literature also implies that quick changeover techniques are often implemented in batch process industries.…”
Section: Type Of Studymentioning
confidence: 99%
“…Literature also implies that quick changeover techniques are often implemented in batch process industries. Set-up times are generally large in process industries in comparison to discrete manufacturing (Gilmore and Smith 1996). In batch type process industries such as food, textile, pharmaceutical and chemical, quick changeover techniques such as single minute exchange of dies (SMED) can be very helpful to reduce set-up times.…”
Section: Type Of Studymentioning
confidence: 99%
“…The market demand for variety in pharmaceutical produce requires greater flexibility, smaller orders and a more varied mix of products within the manufacturing process (Gilmore & Smith, 1996). In response to these demands, the adoption of lean manufacturing has become widespread for pharmaceutical manufacturers (Gebauer et al, 2009).…”
Section: Research Contextmentioning
confidence: 99%
“…Gilmore and Smith 1996;Leshke, 1997;and the Business Advantage Website, 1999) and the same applies to mistake proofing (e.g. Grout, 1997;Dvorak, 1998 andSnell andAtwater, 1996).…”
Section: Introductionmentioning
confidence: 94%